2011
DOI: 10.2174/156652411796268704
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes Derived from Human Bone Marrow Mesenchymal Stem Cells Exert Inhibitory Effects on Osteoblastogenesis

Abstract: The infiltration of adipocytes in osteoporotic patients' bone marrow suggests an important regulatory function of bone marrow fat on the development of aged bone. Therefore, we have examined the effects of adipocytes derived from bone mesenchymal stem cell (MSC) on osteoblast differentiation using two different co-culture modes (direct mode and indirect mode). Alkaline phosphatase (ALP)-positive areas and mineralized areas of MSC-derived osteoblasts decrease similarly in the two co-culture modes as the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…Osteoblasts and adipocytes are derived from stromal cell progenitors and it has been inferred that adipocyte differentiation within the bone marrow reduces, or even precludes, concurrent osteoblast differentiation leading to bone loss [7, 10, 3036]. Our observation that bone marrow adipocyte-deficient kit W/W-v mice have increased osteoblast perimeter is consistent with the view that low levels of adipogenesis increase osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 90%
“…Osteoblasts and adipocytes are derived from stromal cell progenitors and it has been inferred that adipocyte differentiation within the bone marrow reduces, or even precludes, concurrent osteoblast differentiation leading to bone loss [7, 10, 3036]. Our observation that bone marrow adipocyte-deficient kit W/W-v mice have increased osteoblast perimeter is consistent with the view that low levels of adipogenesis increase osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 90%
“…Overexpression of Bmal1 could promote bone mesenchymal stem cell (BMSC) proliferation, and this process was relatively independent of Bmal1 regulation of circadian rhythm, testifying that Bmal1 could inhibit cell aging [12]. Furthermore, the expression of b-catenin, the key factor of Wnt/b-catenin signaling, increased when Bmal1 was overexpressed [13], and another study showed that b-catenin expression decreased with aging [14]. As the main signaling pathway in development, Wnt/b-catenin signaling may play vital roles in the aging process [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSC) residing in the marrow space give rise to cellular populations of the marrow microenvironment, such as osteoblasts and adipocytes. Because of their pluripotent capability, there has long been an assumption MSC phenotype directly influences bone – related parameters, i.e., increasing marrow adipogenesis is inversely proportional with bone mass [7][10]. MSCs additionally act as key regulators of hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%